Optimization of Functional Compositions in Spreading Inhibition - Lame, A.; Sarci, M.; Gace, Z. (Asian Journal of Chemistry, 2011)
The concentration ratio between a selected spreading agent and a selected corrosion inhibitor was optimized to effectively mitigate bottom-of-the-line (BOL) and top-of-the-line (TOL) corrosion under sour gas and aerated conditions. This was performed with electrochemical polarization measurements, electrochemical noise diagnosis and mass loss measurements at low alloy steels in oil field formation brine (i) saturated with 1 bar H2S, (ii) exposed to air and (iii) de-aerated with hydrazine dihydrochloride (N2H4·2HCl) and in the presence of N2 atmosphere above solution. It appeared that the functional system worked well in sour environment at an optimized concentration ratio, however, could not prevent pitting in the air-saturated medium. A new functional system has to be developed for such conditions.